The multidimensional impacts of external price shocks on macroeconomic variables: Malaysian experiences from recession to economic instability - Jaafar, , AH; Yeasmin,, M; Kari,, F; Mazumder, , MNH; Azam, , MN; Al-Amin, , AQ (2011)
The 2008 to 2009 global external price shocks on foods and oil exert worldwide impacts on production, expenditure pattern, trade, welfare, internal resource allocation and ultimate impacts diverted to global recession, Malaysia is not an exception. Centering the world's (2008 to 2009) oil and food price catastrophe, here we investigate Malaysian experiences from recession to economic instability. An applied computable general equilibrium model is utilized in our study to simulate the Malaysian economic impacts by three scenarios. First is food import price increase by 20% (Scenario 1), second is the oil price catastrophe by 40% (Scenario 2) and finally a scenario that combines Scenarios 1 and 2 simultaneously (Scenario 3). Our results depict the multidimensional impacts on major macroeconomic indicators from recession to economic instability. Our results indicate that, price catastrophe either in Scenario 1 or 2, or in Scenario 3, depress overall Malaysian domestic outputs and exports. Reduced output also reduces employment, thus causing a fall in household's income. Overall imports also decreased by 0.2, 1.5, and 1.7% respectively, in all scenarios that specify consumers can afford less quantity of both domestic and imported goods; is the clear indication of recession and economic instability. Our study can be a message to policy makers, who are considering recession and trade policy together.